Catalytic Synthesis of the Biofuel 5-Ethoxymethylfurfural (EMF) from Biomass Sugars. (1st November 2021) - Yu, Dayong; Liu, Xiaofang; Jiang, Jingjing; Liu, Yixuan; Tan, Jinyu; Li, Hu
Abstract : A new generation of bioplatform molecule 5-ethoxymethylfurfural (EMF) has excellent energy density and combustion performance, which makes it a potential fuel additive. This article reviews the factors that affect the production of EMF from different feedstocks, including platform compounds, monosaccharides, polysaccharides, and raw lignocellulosic biomass. Focus is placed on discussing the catalytic efficiency with pros and cons of different acid catalysts, including homogeneous catalysts (i.e., liquid acids and metal salts), heterogeneous catalysts (i.e., zeolites, heteropolyacid-based hybrids, and SO3 H-based catalysts), ionic liquids, mixed acid catalysts, and deep eutectic solvents (DESs). Except for the commonly used ethanol solvent, this review also summarizes the influence of the cosolvent system (e.g., ethanol/dimethylsulfoxide (DMSO), ethanol/tetrahydrofuran (THF), and ethanol/ γ -valerolactone (GVL)) on the EMF yield.